The Influence of Work-Life Balance and Work Motivation on the Performance of Millennial Employees at Bank SUMUT Medan Sukaramai Branch Office - Mastura, Mastura; Lumbanraja, Prihatin; Absah, Yeni (Journal of International Conference Proceedings, 2024)
This research aims to analyze the influence of work-life balance and work motivation on the performance of millennial employees at Bank SUMUT Medan Sukaramai Branch Office. The sample was determined using a saturated sampling technique of 70 respondents. Data collection is carried out by distributing questionnaires. Data analysis uses multiple linear regression analysis. The results of the partial test found that there was a positive and significant influence between work-life balance on employee performance, and organizational work motivation had a positive and significant influence on. employee performance. The results of the simultaneous test found that there was a positive and significant influence between work-life balance and organizational work motivation had a positive and significant influence on. employee performance. Apart from that, it can be seen that the adjusted R square value of the millennial employee performance variable at Bank SUMUT Medan Sukaramai Branch Office. is 0.752, this means that the percentage of influence on work life and work motivation has a significant effect on the performance of millennial employees, namely 75.2%, while the remaining 24.8% is explained by other variables which were not examined in this research.Keywords: "Work-life balance";" Work motivation"; :Millennial Employee Performance:.Â